Identification of novel conserved Ixodes vaccine candidates; a promising role for non-secreted salivary gland proteins. Issue 52 (12th December 2022) - Trentelman, Jos J.A.; de Vogel, Fons A.; Colstrup, Emil; Sima, Radek; Coumou, Jeroen; Koetsveld, Joris; Klouwens, Michelle J.; Nayak, Abhijeet; Ersoz, Jasmin; Barriales, Diego; Tomás-Cortázar, Julen; Narasimhan, Sukanya; et al.
Abstract: Ixodes ricinus and Ixodes scapularis are the main vectors for the causative agents of Lyme borreliosis and a wide range of other pathogens. Repeated tick-bites are known to lead to tick rejection; a phenomenon designated as tick immunity. Tick immunity is mainly directed against tick salivary gland proteins (TSGPs) and has been shown to partially protect against experimental Lyme borreliosis. TSGPs recognized by antibodies from tick immune animals could therefore be interesting candidates for an anti-tick vaccine, which might also block pathogen transmission. To identify conserved Ixodes TSGPs that could serve as a universal anti-tick vaccine in both Europe and the US, a Yeast Surface Display containing salivary gland genes of nymphal I. ricinus expressed at 24, 48 and 72 h into tick feeding was probed with either sera from rabbits repeatedly exposed for 24 h to I. ricinus nymphal ticks and/or sera from rabbits immune to I. scapularis. Thus, we identified thirteen TSGP vaccine candidates, of which ten were secreted. For vaccination studies in rabbits, we selected six secreted TSGPs, five full length and one conserved peptide. None of these proteins hampered tick feeding. In contrast, vaccination of guinea pigs with four non-secreted TSGPs – two from the current and two from a previous human immunoscreening - did significantly reduce tick attachment and feeding. Therefore, non-secreted TSGPs appear to be involved in the development of tick immunity and are interesting candidates for an anti-tick vaccine.